African Economic Integration Initiatives and the Challenge of Responsible Business Conducts: Analysis of Corporate Social Responsibility Provisions in African Regional Trade and Investment Agreements - Azapmo, Jean Bertrand (Revue Interventions économiques / Papers in Political Economy)

(untitled) (Association d’Économie Politique, 2023)
Left alone, economic integration initiatives, which aim to promote growth through investment and trade liberalization, do not automatically generate win-win outcomes for all stakeholders, or lead to the inclusive economic growth and sustainable development of participating countries. This situation which is due among others to possible market failures and externalities of corporations’ activities, has increasingly become a matter of concern with the numerous corruption scandals; human rights violations and environmental degradation involving corporations observed in a recent past. How therefore to continue promoting economic integration while ensuring socially responsible conducts from businesses in societies where they operate? One approach that has recently gained traction is the institutionalization of corporate social responsibility (CSR) clauses in trade and investment agreements. This paper analyses 10 African regional trade and investment agreements concluded between 2000 and 2020 to determine the extent to which they converge with this trend and the approach adopted in regulating CSR. The research complements the literature on the nexus between international law and CSR in the African context.